1988
DOI: 10.1007/bf00141288
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in the terrestrial isopod Porcellio scaber latreille. I. Histochemical and ultrastructural characterization of metal-containing lysosomes

Abstract: Different populations of metal-loaded and uncontaminated Porcellio scaber Latreille were studied. Combined light and electron microscopical methods as well as X-ray microanalysis were applied for localization and characterization of intracellular sites of metal deposition within the small cells of hepatopancreas. By means of cytochemistry and X-ray microanalysis it was shown that membrane-limited vesicles are important sites of deposition for lead, copper, zinc and probably smaller amounts of cadmium. The vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Density gradient centrifugation, marker enzyme tests, and AAS studies additionally revealed evidence for the localization of at least lead, copper, and cadmium in two lysosomal fractions . About 30% (in exposed specimens up to 60%) of the entire lead and 12-30% of the copper in the hepatopancreas of Porcellio scaber are present in these lysosomal fractions, the rest is scattered throughout the cytoplasm Prosi and Dallinger, 1988;Donker et al, 1990). The presence of excess metals in the cytoplasm of hepatopancreatic cells seems to be a general phenomenon, since zinc and cadmium is also deposited throughout the cytoplasm and at the cell membranes, if concentrations in the hepatopancreas of Oniscus asellus exceed 1.5% Zn or 0.5% Cd per dry weight (Hopkin and Martin, 1982a).…”
Section: Woodlice (Isopoda)mentioning
confidence: 98%
See 2 more Smart Citations
“…Density gradient centrifugation, marker enzyme tests, and AAS studies additionally revealed evidence for the localization of at least lead, copper, and cadmium in two lysosomal fractions . About 30% (in exposed specimens up to 60%) of the entire lead and 12-30% of the copper in the hepatopancreas of Porcellio scaber are present in these lysosomal fractions, the rest is scattered throughout the cytoplasm Prosi and Dallinger, 1988;Donker et al, 1990). The presence of excess metals in the cytoplasm of hepatopancreatic cells seems to be a general phenomenon, since zinc and cadmium is also deposited throughout the cytoplasm and at the cell membranes, if concentrations in the hepatopancreas of Oniscus asellus exceed 1.5% Zn or 0.5% Cd per dry weight (Hopkin and Martin, 1982a).…”
Section: Woodlice (Isopoda)mentioning
confidence: 98%
“…According to Dallinger and Prosi (1988) and Prosi and Dallinger (1988), the origin of the type B granules in the S-cells of isopods lies in the lysosomal system. Using cytochemistry and X-ray microanalysis, the authors found lead, copper, zinc, cadmium, and also phosphorus stored in membrane-limited vesicles in the Scells of the hepatopancreas, which presumably are precursors of, or identical with, the type B "cuprosomes."…”
Section: Woodlice (Isopoda)mentioning
confidence: 99%
See 1 more Smart Citation
“…As far as is known heavy metals are stored mainly in the hepatopancreas. This organ consists of B and S cells in which the metals are not only bound to speci"c low-molecular-weight compounds in the cytosol but are also stored in an undissolved nontoxic form in vesicles of lysosomal origin (for further information see Martin, 1982b, 1984;Hopkin, 1989Hopkin, , 1990bProsi and Dallinger 1988;Prosi et al, 1983;Donker et al, 1990). Because B and S cells have di!erent functions, the storage of metals in either one or both of these cell types and the characteristics of the metals themselves are important for the ability of the animals to eliminate them again.…”
Section: Introductionmentioning
confidence: 99%
“…c Regression analysis plot for annual wet deposition (mm) assessed along the transect area across Dornbirn from westnorthwest toward east-southeast as deduced from wet precipitation maps of the government of Vorarlberg (Vorarlberger Landesregierung) and assembled by Werner (2011). For regression analysis parameters attributed to plots a, b, and c, see Table 3 terrestrial isopods is influenced by metal and species-specific physiological pathways (Prosi and Dallinger 1988;Hopkin 1989;Dallinger 1993;Witzel 2000;Beeby 2001) as well as site-specific ecological and geochemical features (Hopkin 1990;Gál et al 2008;Vermeulen et al 2009). Moreover, the outcome of such studies often depends on the methodological procedure chosen, including factors such as season, time span, and method of collecting, as well as sample homogeneity, storage, and preparation (Wieser et al 1977;Hendrickx et al 2003).…”
Section: Hg Concentrations In Isopods Correlate With Soil Substrate Lmentioning
confidence: 99%